Comparative study on the diversity of endophytic actinobacteria communities from Ficus deltoidea using metagenomic and culture-dependent approaches - ISRA JANATININGRUM; DEDY DURYADI SOLIHIN; ANJA MERYANDINI; YULIN LESTARI (Biodiversitas Journal of Biological Diversity, 2018)
Janatiningrum I, Solihin DD, Meryandini A, Lestari Y. 2018. Comparative study on the diversity of endophytic actinobacteria communities from Ficus deltoidea using metagenomic and culture-dependent approaches. Biodiversitas 19: 1514-1520. Actinobacteria endophytes of medicinal plants may play an essential role in producing a variety of critical bioactive compounds. However, the possible contribution of such actinobacteria to the pharmacological properties of traditional herbal remedies remains mostly unknown. For example, the diversity and attributes of actinobacteria endophytes in Ficus deltoidea, a small tree species that has long been used to treat diseases such as cancer, diabetes, and cardiovascular illnesses, have not been explored. Here, the actinobacteria endophyte community structure in F. deltoidea was investigated using both culture-dependent and metagenomics approaches. Based on morphological characteristics and 16S rRNA gene analysis, the dominant culturable actinobacteria isolates exhibited a close relationship with Streptomyces. The metagenomic technique using PCR-DGGE analysis of the 16S rRNA gene showed the presence of 11 OTUs in F. deltoidea tissue. Whereas the dominant culturable actinobacteria endophytes in F. deltoidea was Streptomyces, the metagenomic approach showed non-Streptomyces, particularly Rhodococccus and Verrucosispora, to be also important. Thus, results from both culture-dependent and metagenomic approaches provided useful indicators on the diversity and community structure of actinobacteria endophytes in F. deltoidea.